Using Simulation of Single Stage Refrigeration Cycle in Teaching - Lê Xuân Hòa; Đoàn Minh Hùng (Journal of Technical Education Science, 2006)
In this paper, we simulated three single stage refrigeration cycles by using Macromedia Director that are: Single stage refrigeration cycle perform the dry stroke, Single stage refrigeration cycle perform the dry stroke by using suction line accumulator and Single stage refrigeration cycle by using heat exchanger.